2019
DOI: 10.5114/pm.2019.84154
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of HE4 protein in differentiation of pelvic masses in woman

Abstract: Introduction: HE4 protein (human epididymis protein-4), which is the fourth subfraction of human epithelial protein, is a glycoprotein widely used as a tumor marker in ovarian cancer. If was first discovered in the epididymal epithelium and recognized as a protease inhibitor contributing to sperm maturation. The plasma HE4 concentration may also be increased in gynecological pathologies other than ovarian cancer. Material and methods: The study was conducted between 2016 and 2017 among patients hospitalized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In 2008, the US Food and Drug Administration (FDA) identi ed HE4 as a serum marker for monitoring recurrence and progression in epithelial ovarian cancer (EOC) patients. Thereafter, HE4 started gradually stirring more and more attention; several studies have demonstrated the usefulness of HE4 in the early diagnosis of EOC and the identi cation of pelvic masses, especially when used in combination with the risk of ovarian malignancy algorithm (ROMA); moreover, HE4 exhibited higher sensitivity and speci city than its predecessors, including CA125 3,18 . In terms of function and mechanism, HE4 can promote the proliferation, invasion, metastasis, and drug resistance of ovarian cancer cells 10,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, the US Food and Drug Administration (FDA) identi ed HE4 as a serum marker for monitoring recurrence and progression in epithelial ovarian cancer (EOC) patients. Thereafter, HE4 started gradually stirring more and more attention; several studies have demonstrated the usefulness of HE4 in the early diagnosis of EOC and the identi cation of pelvic masses, especially when used in combination with the risk of ovarian malignancy algorithm (ROMA); moreover, HE4 exhibited higher sensitivity and speci city than its predecessors, including CA125 3,18 . In terms of function and mechanism, HE4 can promote the proliferation, invasion, metastasis, and drug resistance of ovarian cancer cells 10,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The human epididymis protein-4 (HE4) encoded by the WAP four-disulfide core domain 2 gene is also a glycoprotein and commonly used as a tumor marker in OC. Its plasma levels are increased in gynecological pathologies and are useful in prognosis as well as in assessing the degree of differentiation and clinical progression of OC [40] . Dewan et al [41] compared the sensitivity and specificity of H4 values with those of CA125 using serum samples from OC patients and patients with benign ovarian diseases.…”
Section: He4mentioning
confidence: 99%
“…Since then, more and more investigators are paying attention to it. Multiple studies found that HE4 is a useful biomarker possessing higher sensitivity and speci city than CA125 in the early con rmatory diagnosis for EOC and differentiation of pelvic masses, especially in combination with the risk of ovarian malignancy algorithm (ROMA) [12,13]; it seems to be a good predictive factor for the ideal tumor cytoreductive surgery [3], pre-operative prediction of residual disease after interval cytoreduction [4], adjuvant chemotherapy resistance [14] and the possibility of ascites formation [15].…”
Section: Introductionmentioning
confidence: 99%